Ion exchange - Muraviev, Dimitri 1948-; Warshawsky, Abraham; Gorshkov, V. I. (Highlights of Russian science, 2000)
This text offers the best of ion exchange science conducted in the countries of the former Soviet Union. It reviews the multidisciplinary study at the nexus of physical, organic, inorganic and biological chemistries, and progresses from theoretical fundamentals to practical applications in manufacturing, mineral refining and environmental clean-up. The text examines advances and phenomena observed in ion-exchange systems.